Antibody-drug conjugates in treating older patients suffering from cancer: what is the real value?. Issue 12 (2nd December 2021) - Perego, Gianluca; Ghidini, Antonio; Luciani, Andrea; Petrelli, Fausto
ABSTRACT: Immunotherapeutic drugs and target therapies have represented an epochal change in treating cancer patients. They represent an attractive option in oncologists' armamentarium, particularly if we consider the optimal balance between efficacy and toxicity. As a step forward, immuno- and target-therapies have merged intending to improve efficacy: antibody-drug conjugates ensure the perfect combination. They allow the delivery of large amounts of drugs to the target with a limited 'off-target' effect and a low rate of adverse events. These aspects could make immunoconjugates palatable as the first choice for fragile patients, but solid evidence does not exist on the use of these drugs in this population type, especially older people.